Using the internet as a Collective Intelligence platform in harnessing issues on climate change - Gunasekaran S.S.; Mostafa S.A.; Ahmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
The Emergence of WEB 2.0 and social media technologies facilitates many social computing applications such as THREADLESS, WIKIPEDIA, GOOGLE and much more as a gateway of mediums in which vast amount of data is shared and discussed globally. These new internet technology platforms multiple broadways in which problems are shared and discussed, thus leveraging patron's globally to contribute collective synergy solutions. Subsequently, its intelligent revolution is aiding in solving world related problems. This paper discusses the topology of the collective intelligent mechanism and its influence in the internet technology. It provides a case structure of how CI is used as an online mechanism in improving issues related to climate change. As such the paper looks at the notion of Collective Intelligence from the perspectives of Social Sciences. It discusses the current state of climate change worldwide and shows evidence of how the matter of climate change can be solved collectively. © 2014 IEEE.